Innovation policy and the economy. - Jaffe, Adam B.; Lerner, Joshua; Stern, Scott, 1969- (Innovation policy and the economy., 2006)
The economic importance of innovative activity brings with it an active debate on public policy's effect on the innovation process. This annual series, sponsored by the National Bureau of Economic Research, brings the work of leading academic researchers to the broader policy community. Volume 6 considers such topics as the diversity of patent protection and the implications of weak patents for innovation and competition; reforms in U.S. patent policy that will encourage innovation; the multifaceted benefits of the Internet for consumers, including price competition and novel forms of communication; the drug development and approval process; the "offshoring" of research and development; and the advantages of industry-specific studies of the relationship between innovation and competition. The papers highlight the role economic theory and empirical analysis can play in evaluating current and prospective innovation policy alternatives